Penerapan Pendidikan Literasi Finansial terhadap Kemandirian Peserta Didik dalam Mengelola Beasiswa Program Indonesia Pintar - Parada Monita Napitupulu; Henny A. Manafe; M.E. Perseveranda; Agapitus Hengky Kaluge; Thomas Ola Langoday (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This article discuss why and how financial literacy education is very important for students. Inculcating the value of financial literacy in students will greatly affect the understanding and knowledge of financial literacy and also the level of welfare in the future. The role of schools is also very important in providing knowledge about literacy education to students. The cognitive nature of students who are still concrete and are still in the development stage is very effective in instilling the value of financial literacy, with the aim that students who get the PIP (Smart Indonesia Program) scholarship should be able to manage their finances properly, according to their needs and needs as students. The current situation of students who tend to make purchases without paying attention to financial principles so that it can result in irrational buying of their needs. It is necessary to develop a learning design that embraces the dimensions of knowledge and understanding, skills and attitudes regarding financial literacy which will ultimately produce learning objectives and outcomes for the improvement of students' understanding for the future.